4-(3-Methoxyphenyl)-3-[2-(4-methoxyphenyl)ethyl]-1H-1,2,4-triazol-5(4H)-one - Hanif, Muhammad (International Union of Crystallography, 2009)
The asymmetric unit of the title compound, C(18)H(19)N(3)O(3), contains two crystallographically independent but similar molecules. The triazole ring is oriented with respect to the benzene rings to form dihedral angles of 57.96 (6) and 7.01 (6)° in one molecule, and 64.37 (5) and 10.73 (5)° in the other. The two independent molecules are linked into a dimer by intermolecular N—H⋯O hydrogen bonds.